No evidence for a survival difference between upper and lower lip squamous cell carcinoma. Issue 5 (May 2015) - Pietersma, N.S.; de Bock, G.H.; de Visscher, J.G.A.M.; Roodenburg, J.L.N.; van Dijk, B.A.C.
Abstract It is generally assumed that upper lip cancer has a worse survival than lower lip cancer, but this notion is not convincingly supported by limited literature. Therefore, we tested whether upper lip cancer has a worse survival than lower lip cancer. All primary squamous cell carcinoma (SCC) of the lip in the North-East of the Netherlands from 1989-2009 were extracted from the Netherlands Cancer Registry database. We calculated overall and relative survival rates. In this series of 979 lower lip and 126 upper lip SCC, men were 2.6 times more often affected, while the proportionate share of upper lip cancer was larger in women. The 5-year overall survival for lip cancer equaled 74% (95% confidence interval (CI) 70–77%), while the relative survival equaled 97% (95% CI 93–100%). The overall and relative 10-year survival rates were 51% (95% CI 47–54%) and 90% (95% CI 84–96%), respectively. The 10-year relative survival rate for patients with SCC of the upper lip was 94% (95% CI 74–111%) compared to 90% (95% CI 83–96%) for patients with SCC of the lower lip. There appears to be little evidence that patients with upper lip SCC have a worse survival rate.